Comparative analysis of maize hybrides grown for bioethanol production purposes - Bánszki, Lívia (Acta Agraria Debreceniensis, 2012)
The objective of this study was to evaluate the effects of crop year on the main components of maize grown for bio-ethanol production yield, starch content and starch yield per hectare of maize hybrids were investigated in a droughty (2007) and in a favourable years with optimal weather conditions (2008, 2009). We measured very low starch yield (1.5 t ha-1) in the year with unfavourable precipitation supply (2007) together with higher starch content (73%). In the case of good precipitation supply we measured a much higher starch yield per hectare (7.7 t ha-1) with lower content (72.4%). In 2009 the starch content (74.5%) exceed the results of the two previous years, but on the other hand the average of starch yield was (4.9 t ha-1) which falls between the other two years values.